Pars Plana Vitrectomy for Proliferative Diabetic Retinopathy With and Without Internal Limiting Membrane Peeling: A Case Series: Poster Presentation - Case Series - Resident - WISESAPUTRA, TJOK AGUNG PURNAMA; Panjawati, Sp.M(K), dr. Ni Luh Diah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Proliferative Diabetic Retinopathy (PDR) is a potentially blinding complication of diabetes mellitus, one of them because of tractional retinal detachment. Pars Plana Vitrectomy (PPV) is performed to treat it and in recent years internal limiting membrane (ILM) peeling has been employed as an additional treatment for patient with PDR. Case Illustration : Two patient, patient 1 (male, 64 years old) was diagnosed with right eye vitreous hemorrhage due to high-risk PDR and left eye vitreous hemorrhage due to early PDR + DME, and patient 2 (female, 58 years old) was diagnosed with right and left eye PDR + ERM + senile immature cataract. Both patients underwent PPV + membrane peeling + endolaser for both eyes, and additional ILM peeling on their left eye. The visual acuity 1 month after surgery without ILM peeling on right eye was improved to 6/30 and 6/18, and with ILM peeling on left eye was improved to 6/30 for both patients. Discussion : Removal of the ERM either with or without ILM peeling can significantly improve vision. However, many other comparison studies found no functional difference between both groups. In addition, one study found ILM removal was correlated with worse visual outcome. In this study, visual acuity 1 month after surgery in both with and without ILM peeling was improved compared with pre- operative. Conclusion : Although there are still pros and cons, PPV with additional ILM peeling gives results as good as PPV without ILM peeling for patient with PDR.